2019
DOI: 10.1038/s41467-019-09900-9
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni treatment reduces HIV entry into cervical CD4+ T cells and induces IFN-I pathways

Abstract: Schistosoma mansoni ( Sm ) infection has been linked with an increased risk of HIV acquisition in women. Therefore, defining the mechanism(s) by which Sm alters HIV susceptibility might lead to new HIV prevention strategies. Here, we analyze the impact of standard Sm therapy in HIV-uninfected Sm + Ugandan adult women on genital HIV susceptibility and mucosal and systemic immunology. Schistosomiasis treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…In keeping with the earlier studies, our recent work [226] provides support for future clinical studies of S. mansoni treatment as an HIV prevention strategy. Specifically, we found that S. mansoni treatment resulted in an over two- fold reduction of ex vivo HIV entry into genital and blood CD4 T cells, but surprisingly this reduced virus entry after praziquantel therapy was accompanied by transient immune activation in the cervix and blood.…”
Section: Could the Treatment Of Endemic Infections Reduce Hiv Susceptsupporting
confidence: 77%
See 2 more Smart Citations
“…In keeping with the earlier studies, our recent work [226] provides support for future clinical studies of S. mansoni treatment as an HIV prevention strategy. Specifically, we found that S. mansoni treatment resulted in an over two- fold reduction of ex vivo HIV entry into genital and blood CD4 T cells, but surprisingly this reduced virus entry after praziquantel therapy was accompanied by transient immune activation in the cervix and blood.…”
Section: Could the Treatment Of Endemic Infections Reduce Hiv Susceptsupporting
confidence: 77%
“…While it is logical that intestinal schistosomiasis would have a direct effect on HIV transmission after sexual exposure in the rectal mucosa, helminth-induced gut mucosal inflammation could theoretically involve other mucosal sites (such as the female lower genital tract) through activation of the common mucosal immune system [79]. In keeping with this, S. mansoni -infected women with a higher parasite burden demonstrated elevated expression of the mucosal homing integrin α4β7 on blood CD4+ T cells [226], which would be expected to home these CD4 cells to the gut and cervical mucosa. However, this integrin does not appear to home T cells to the foreskin, the predominant site of HIV acquisition in heterosexual men from SSA, since the predominant integrin expressed on T cells in foreskin tissues is cutaneous lymphocyte antigen (CLA) [48].…”
Section: Schistosomiasis and Hiv Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mature blood flukes living in the vasculature lay eggs, which become deposited in host tissues, where they trigger local inflammatory responses. Chronic infections become associated with fibrosis and obstructive disease in gastrointestinal tissues and liver ( Schistosoma mansoni , Schistosoma japonicum ), genitourinary disease ( Schistosoma haematobium ), anemia, undernutrition, and a heightened risk for other comorbidities (3). The annual disease burden has been estimated as a loss of up to 70 million disability-adjusted life years (1, 2).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, individuals with S . mansoni infection had increased expression of α4β7 on blood CD4+ T cells [13], and increased pre-HIV infection expression of α4β7 has been associated with higher set-point plasma viral loads [14]. Lastly, female schistosomes lay hundreds of eggs per day that can become deposited in host female genital organs, triggering an inflammatory response with recruitment of leukocytes to the genital epithelium [1517].…”
Section: Introductionmentioning
confidence: 99%